Factors Affecting The Level Of Anxiety Of Primigravida Mothers In Facing Labor At Batara Siang Pangkep Hospital - Ani; Astri Yuliandini; Mauren Tenine (Indonesian Journal of Nursing and Health Care, 2025)
Background: Primigravida labor refers to childbirth in first-time pregnant women, who tend to experience longer labor pain compared to multigravida mothers. This prolonged pain often leads to fatigue, heightened pain perception, and increased fear, which can further intensify labor pain. As a result, primigravida mothers may suffer from severe anxiety, leading to difficulties in eating, sleeping, and even an increased risk of preterm birth.Objective: This study aims to identify the factors influencing the anxiety levels of primigravida mothers during childbirth.Methods: This study employs a quantitative research approach with a cross-sectional study design. The population consists of 25 primigravida mothers who gave birth at Batara Siang Pangkep Regional Hospital, selected using purposive sampling. Data collection was conducted using a questionnaire designed to assess factors influencing maternal anxiety levels during childbirth.Results: Statistical analysis revealed significant associations between maternal age (p = 0.002 < 0.05), maternal knowledge (p = 0.022 < 0.05), and family support (p = 0.002 < 0.05) with the anxiety levels of primigravida mothers.Conclusion: The study concludes that maternal age, knowledge, and family support are significantly associated with the anxiety levels of primigravida mothers during childbirth at Batara Siang Pangkep Regional Hospital in 2022. Strengthening educational and emotional support for first-time mothers is essential to reducing anxiety and improving maternal well-being during labor.